Organic Solvents as Vehicles for Precipitating Liquid Embolics: A Comparative Angiotoxicity Study with Superselective Injections of Swine Rete Mirabile - Dudeck, O. (AJNR Am J Neuroradiol, 2006)
BACKGROUND AND PURPOSE: The organic solvent dimethyl-sulfoxide (DMSO), as a commonly used vehicle for nonadhesive liquid embolics, is not devoid of local angiotoxic effects. We compared microvascular toxicities of superselective infusions of DMSO with potentially more compatible solvents in swine rete mirabile. METHODS: Fourteen swine underwent angiography for superselective catheterization of 28 arteries of the rete while electrocardiography and intra-arterial pressure were continuously monitored. The investigated solvents were DMSO, dimethyl isosorbide (DMI), ethyl lactate, glycofurol 75, N-methyl pyrrolidone (NMP), and solketal. Control infusion of saline ruled out catheter induced vasospasm in all cases. Each artery of the rete was infused only once with 0.8 mL of one of the solvents over 60 seconds. Acute angiographic and hemodynamic consequences were evaluated. Blood samples were assessed for signs of intravascular hemolysis. Brains and retia were harvested for gross and histopathologic investigation. RESULTS: On the basis of the angiographic data, DMSO induced the most pronounced vasospasm with the longest recovery period of all solvents investigated. Ethyl lactate, glycofurol 75, and solketal elicited less severe vasospasms and accordingly resolved much more quickly. DMI and NMP induced only minimal vasospasms with comparably short duration. No solvent caused significant hemodynamic alterations or hemolysis. Gross inspection of brains showed no abnormalities, whereas histopathologic examination revealed mostly nonspecific findings. One rete exposed to solketal displayed possible causal histotoxic changes. CONCLUSION: DMI and NMP produced far less vasospasm than DMSO. No changes in hemodynamic or hemolytic parameters and no histopathologic findings were observed with infusion of these solvents.